Further Convergence Management to Build a More Resilient Education System for International Students at Tsinghua University in COVID-19 Pandemic Period - Liu, Qingling; Zou, Nan (Journal of International Students, 2022)
COVID-19 disrupts regular educational order and poses significant challenges to international education. In the face of the uncertain development of the pandemic, Tsinghua University has been actively exploring to build a more resilient education system by further promoting convergence management of the local and international students. Based on the organization system theory, we explain the necessity of convergence management, review Tsinghua’s responses to the COVID-19 crisis, and introduce the practices in building a more resilient education system, and discuss the future for promoting system resilience.